2017
DOI: 10.1002/cjoc.201600888
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)‐Catalyzed Three‐Component Coupling of Trifluoromethyl KetoneN‐Tosylhydrazones, Alkynes and Azides: Synthesis of Difluoromethylene Substituted 1,2,3‐Triazoles

Abstract: A CuI-catalyzed three-component coupling of trifluoromethyl ketone N-tosylhydrazones, alkynes and azides has been developed. The reaction represents a straightforward method to access difluoromethylene substituted 1,2,3-triazoles. Mechanistically, it has been proposed that the reaction follows a pathway involving the formation of Cu(I) triazolide intermediate, Cu(I) carbene formation, migratory insertion, and β-fluoride elimination. The transformation is featured by mild conditions, wide substrate scope and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Recently, Wang and co-workers disclosed that the use of trifluoromethyl ketone derived N -tosylhydrazones as substrates would produce difluoromethylene substituted 1,2,3-triazoles ( 606 ) . Instead of protonation process, a β-fluoride elimination occurs exclusively to finish the catalytic cycle in this transformation (Scheme b).…”
Section: Cu-catalyzed Carbene Coupling Reactionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, Wang and co-workers disclosed that the use of trifluoromethyl ketone derived N -tosylhydrazones as substrates would produce difluoromethylene substituted 1,2,3-triazoles ( 606 ) . Instead of protonation process, a β-fluoride elimination occurs exclusively to finish the catalytic cycle in this transformation (Scheme b).…”
Section: Cu-catalyzed Carbene Coupling Reactionsmentioning
confidence: 78%
“…Recently, Wang and co-workers disclosed that the use of trifluoromethyl ketone derived N-tosylhydrazones as substrates would produce difluoromethylene substituted 1,2,3-triazoles (606). 301 Instead of protonation process, a β-fluoride elimination occurs exclusively to finish the catalytic cycle in this transformation (Scheme 90b). These two reactions serve as good examples on the combination of click chemistry with carbene coupling process and provide a general methodology to access highly functionalized 1,2,3-triazoles in a regioselective manner.…”
Section: Reaction With Other Coupling Partnersmentioning
confidence: 99%
“…They continued to explore an efficient and regioselective method for the synthesis of difluoromethylene substituted 1,4,5‐trisubstituted 1,2,3‐triazoles 194 through CuI‐catalyzed three‐component coupling of trifluoromethyl ketone N ‐tosylhydrazones 191 , alkynes 192 and azides 193 in 2017 (Scheme 30). [61] Mechanistically, they proposed that the reaction follows a cascade process involving the formation of [2+3] cycloaddition, Cu(I) carbene formation, migratory insertion, and β ‐fluoride elimination.…”
Section: Surrogates Of Trifluoro Diazo Compoundsmentioning
confidence: 99%
“…96 Furthermore, they found that CF 3 -bearing N-tosylhydrazones with other substrates could undergo [3 + 2] cycloaddition and a consequent fluorine elimination pathway to generate multisubstituted 5-(difluoromethylene)-1,2,3-triazoles (Scheme 32). 97 Under the promotion of copper and a base, terminal alkynes and azides undergo a In 2020, Koenig and colleagues demonstrated that 2,2,2-trifluorodiazo derivatives could undergo a C-H bond insertion and C-F functionalization reaction with indoles at room temperature under palladium-catalyzed conditions, allowing for the direct one-step synthesis of gem-difluoroolefin analogues. They proposed a reasonable reaction pathway.…”
Section: C-h Bond Insertion and Gem-difluoroalkenylationmentioning
confidence: 99%
“…96 Furthermore, they found that CF 3 -bearing N -tosylhydrazones with other substrates could undergo [3 + 2] cycloaddition and a consequent fluorine elimination pathway to generate multisubstituted 5-(difluoromethylene)-1,2,3-triazoles (Scheme 32). 97 Under the promotion of copper and a base, terminal alkynes and azides undergo a click transformation to produce copper triazolide intermediate A via metalation of the triazole C–H bond. Then this intermediate A is trapped by trifluoromethyl N -tosylhydrazone 77 to produce copper-complex B , which is followed by the 1,2-shift of triazole and β-fluoride elimination to give corresponding products 101 via intermediate C .…”
Section: Synthesis Of Gem-difluoroalkenesmentioning
confidence: 99%